Artificial neural network model and fuzzy logic control of dissolved oxygen in a bioreactor - Nor Hana Mamat; Samsul Bahari Mohd Noor; Laxshan A/L Ramar; Azura Che Soh; Farah Saleena Taip; Ahmad Hazri Ab. Rashid (Institute of Advanced Engineering and Science, 2020)
In a fermentation process, dissolved oxygen is the one of the key process variables that needs to be controlled because of the effect they have on the product quality. In a penicillin production, dissolved oxygen concentration influenced biomass concentration. In this paper, multilayer perceptron neural network (MLP) and Radial Basis Function (RBF) neural network is used in modeling penicillin fermentation process. Process data from an industrial scale fed-batch bioreactor is used in developing the models with dissolved oxygen and penicillin concentration as the outputs. RBF neural network model gives better accuracy than MLP neural network. The model is further used in fuzzy logic controller design to simulate control of dissolved oxygen by manipulation of aeration rate. Simulation result shows that the fuzzy logic controller can control the dissolved oxygen based on the given profile.